2006
DOI: 10.1002/pca.919
|View full text |Cite
|
Sign up to set email alerts
|

Headspace–solid‐phase microextraction fast GC in combination with principal component analysis as a tool to classify different chemotypes of chamomile flower‐heads (Matricaria recutita L.)

Abstract: Headspace-solid-phase microextraction gas chromatography-principal component analysis (HS-SPME GC-PCA) is proposed as a complementary or alternative method to essential oil (EO) GC-PCA in order to discriminate between flower-heads of chamomile of different chemotypes. Ninety-two EOs and the headspaces sampled by HS-SPME of the corresponding chamomile flower-heads were examined by conventional GC and fast GC (F-GC) and the results submitted to statistical analysis by PCA. HS-SPME F-GC-PCA showed itself to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
1
35
0
2
Order By: Relevance
“…Comparative studies of MWHD and conventional hydrodistillations have showed that the resulting essential oils have very similar chemical composition and that in some cases, the relative content of oxygenated compounds is slightly higher in the MWHD oils 5, 22, 23. The establishment of similarities and differences within groups of complex mixtures such as essential oils is facilitated by multivariate statistical tools such as PCA 5, 24–26. The L. origanoides essential oil composition table in our previous publication 9 included just 22 substances, those with relative amount higher than 0.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative studies of MWHD and conventional hydrodistillations have showed that the resulting essential oils have very similar chemical composition and that in some cases, the relative content of oxygenated compounds is slightly higher in the MWHD oils 5, 22, 23. The establishment of similarities and differences within groups of complex mixtures such as essential oils is facilitated by multivariate statistical tools such as PCA 5, 24–26. The L. origanoides essential oil composition table in our previous publication 9 included just 22 substances, those with relative amount higher than 0.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Headspace volatile compounds analysis Volatile compounds of P. longiflora (PL‐batch 1) and L. graveolens (LG‐batch 2) were separated and identified using solid‐phase microextraction (SPME) system (Yousif and others 2000; Rubiolo and others 2006). One centimeter long poly(dimethylsiloxane)‐coated fibers (Table 2 and 3; 100 μm; Supelco Technology, St. Louis, Mo., U.S.A.) were used for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The most widely used statistical tool for GC profile elaboration is multivariate analysis (MVA), and in particular principal component analysis (PCA), a method that can highlight differences among the samples of a set characterized by a suitable number of components (variables) through the linear combination of those explaining most of the variability. 4,5 In this case, the more samples are analysed, the better is the reliability of the statistical results obtained. Figure 2 reports the PCA discrimination of 92 chamomile (Matricaria recutita L.) EOs by chemotype, using normalized % abundances of seven characterizing sesquiterpenoid components after normalization to a single internal standard (n-tridecane) and standardization of variables.…”
Section: Statistical Elaboration Of the Gc Profilementioning
confidence: 99%